Learning to teach social scien-ces with methods of inquiry. Case studies in the teacher training program - Cosme Jesús Gómez Carrasco; Raimundo A. Rodríguez Pérez (Universitat Politècnica de València, 2014)
The aim of this paper is to show an innovative  experience  in  Primary Teacher  training  for  the  acquisition of  programming  skills  and  planning interactive activities for teaching social sciences. This proposal was launched in the  subject  Didactic  methodology  for teaching social sciences, offered in 3rd year of Primary Education. This course had an impact on the transformation of society has undergone in recent years requires  social  science  teachers  to  a reframing  training  to  enable  them  to meet some new learning environments. Teaching  methods  should  have  as  its main purpose the student to discover and assimilate the environment in which it lives, given the complexity of social facts in all their meaning and nuances. The  case  study  method  to  develop these premises, since it brings a reality to a group of learners. In a series of practical classes students had to raise educational  activities  on  a  specific topic of social sciences in the Primary classroom.  Students  should  propose activities which would analyze the case, identify the problems, find information, compare ideas and defend them in a debate to take the appropriate decisions. Students  appreciated  the  usefulness of this method when proposals lead to classroom teaching in which scientific knowledge school become socially useful knowledge.